Antibody Targets and Properties for Complement-Fixation Against the Circumsporozoite Protein in Malaria Immunity - Kurtovic, Liriye; Drew, Damien R.; Dent, Arlene E.; Kazura, James W.; Beeson, James G. (Frontiers in Immunology, 2021)
The Plasmodium falciparum circumsporozoite protein (CSP) forms the basis of leading subunit malaria vaccine candidates. However, the mechanisms and specific targets of immunity are poorly defined. Recent findings suggest that antibody-mediated complement-fixation and activation play an important role in immunity. Here, we investigated the regions of CSP targeted by functional complement-fixing antibodies and the antibody properties associated with this activity. We quantified IgG, IgM, and functional complement-fixing antibody responses to different regions of CSP among Kenyan adults naturally exposed to malaria (n=102) and using a series of rabbit vaccination studies. Individuals who acquired functional complement-fixing antibodies had higher IgG, IgM and IgG1 and IgG3 to CSP. Acquired complement-fixing antibodies targeted the N-terminal, central-repeat, and C-terminal regions of CSP, and positive responders had greater antibody breadth compared to those who were negative for complement-fixing antibodies (p<0.05). Using rabbit vaccinations as a model, we confirmed that IgG specific to the central-repeat and non-repeat regions of CSP could effectively fix complement. However, vaccination with near full length CSP in rabbits poorly induced antibodies to the N-terminal region compared to naturally-acquired immunity in humans. Poor induction of N-terminal antibodies was also observed in a vaccination study performed in mice. IgG and IgM to all three regions of CSP play a role in mediating complement-fixation, which has important implications for malaria vaccine development.